Reclaiming our roots ; v. 1 an inclusive introduction to church history - Ellingsen, Mark, 1949- (Harrisburg, PA Trinity, 1999)
Contents : v. 1 : the late first century to the eve of the reformation. Includes bibliographical references, indexes, maps.
Keywords: Church history